The Catholic School Culture in the Context of Salesian Pedagogy - Stanisław Chrobak (Nicolaus Copernicus University in Toruń, 2016)
Man creates culture, but it shapes his life. The symbol of the place of education in culture is the school. The cultural identity of the school usually consists of a few basic elements. It is a multi-layered phenomenon, and the values, norms, beliefs and symbols that underlie behaviour of circles related to the school do not always coincide with the values and norms declared in the school's official documents and declarations. In the end, the Catholic school organizes the whole of human culture in accordance with the message of salvation, so that the knowledge that pupils gradually acquire with regard to the world, life and humanity, is illuminated by faith. The Salesian School is embedded in the mission of the Church. Documents of the Salesian Society emphasize that the Salesian school was established in the Oratory in Valdocco (Turin) to respond to the specific needs of young people and engage in widespread programme of education and evangelization of the young, especially the poorest. The mission of the Salesian school: To educate "honest citizens and good Christians", is an essential tool for shaping its cultural identity; it sets out the basic objectives, values and principles of action, expressed in a specific way, that orient its daily activity.